Growth with Exhaustible Natural Resources: Efficient and Optimal Growth Paths - Stiglitz, Joseph (Review of Economic Studies, 1974)
The proposition that limited natural resources provide a limit to growth and to the sustainable size of population is an old one. The natural resource that was the centre of the discussion in Malthus' day was land; more recently, some concern has been expressed over the limitations imposed by the supplies of oil, or more generally, energy sources, of phosphorus, and of other materials required for production. Those who predicted imminent doom in the nineteenth century were obviously wrong. Were they simply wrong about the immediacy of catastrophe, or did they leave out something fundamental from their calculations? There are at least three economic forces offsetting the limitations imposed by natural resources: technical change, the substitution of man-made factors of production (capital) for natural resources, and returns to scale. This study is an attempt to determine more precisely under what conditions a sustainable level of per capita consumption is feasible, to characterize steady state paths in economies with natural resources, and to describe the optimal growth path of the economy, in particular to derive the optimal rate of extraction and the optimal savings rate in the presence of exhaustible natural resources.